Attitudes of secondary school pupils towards the teaching and learning of science: a Zimbabwean case - Gudyanga, Ephias; Gudyanga, Anna (International Journal Advances in Social Science and Humanities, 2016)
The study sought to investigate the attitudes of Zimbabwean secondary school pupils towards the teaching and learning of science. A randomized sample of 243 participants from eight (8) selected schools completed a 5 point Likert type scale. Factorial Analysis using principal components with Varimax Rotation, Kaiser Normalisation and Scree testing were used to determine validity of the scale. Variables with factor loading of 0.3 and above and Eigen values of 1 and above were considered to form main Attitude towards Science (ATS) scale. Data were analyzed using ANOVA and One way ANOVA. It was found out that pupils in lower classes (Forms 1 and 2) recorded a positive attitude towards science than pupils in the upper classes (Forms 3 and 4). There may be a need to re-examine the reasons why attitude declines with form level. Further studies may look at linkage between pupil’s attitude with their science performance in class, career aspirations and perceptions of the world of science at work.